Student Perceptions of an Online Ungraded Course - Guberman, Daniel (Teaching and Learning Inquiry, 2021)
What do grades mean? What purpose do they serve? What role do they play in the learning process? Teachers and scholars have recently begun to re-examine these questions central to our current grading system. As a result, many have started to re-assess how grades are assigned in their classes. In this case study, I examine the effectiveness of ungrading, an approach centered around students assigning their own grades through reflecting on the learning process. After contextualizing and describing the approach developed for this fully online, asynchronous history class, I share quantitative and qualitative data regarding student perceptions, motivation, and information usage to argue that systems such as ungrading have potential for contributing to the construction of highly effective and meaningful learning environments.